2012
DOI: 10.1002/pbc.24447
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fracture as the presenting feature in pediatric osteosarcoma

Abstract: Osteosarcoma complicated by pathological fracture as first presentation had higher incidence of lung and bone metastases at presentation and worse survival rate when compared with patients without pathological fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 15 publications
4
27
2
Order By: Relevance
“…This result is consistent with the findings of most other authors [14, 15, 30, 31]. In contrast, recent data demonstrated a higher rate of metastases in patients with OS and PF [16, 32]. …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This result is consistent with the findings of most other authors [14, 15, 30, 31]. In contrast, recent data demonstrated a higher rate of metastases in patients with OS and PF [16, 32]. …”
Section: Discussionsupporting
confidence: 68%
“…We hereby corroborate the data of Scully et al [28] who observed a significantly higher rate of local recurrences in patients with PF. However, it is of note that in our study the rate of amputation is only 9%, while other authors report on rates between 20 and 60% [14, 16, 18, 31, 28]. Furthermore, other studies report on higher rates of amputation in the fracture group compared to the nonfracture group [14, 30], which is not consistent with our findings (Table 2).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, metaphyseal osteosarcoma in children has been widely considered as a contraindication for limb salvage surgery (2). First, pathological fracture results in loss of the surgical border of the tumor; thus, radical or wide resection cannot be performed (5,6). Second, reconstruction with prosthetic replacement is not suitable for children who have yet to reach skeletal maturity.…”
Section: Introductionmentioning
confidence: 99%